Pengaruh Fitoremediasi dengan Kombinasi Tanaman pada Kadar BOD dan COD Limbah Sasirangan - Adzani Ghani Ilmannafian; Muhammad Indra Darmawan; Mariatul Kiptiah (Jurnal Teknologi Agro-Industri, 2022)
Most of sasirangan craftsmen in South Kalimantan have not carried out an optimal liquid waste treatment effort. In order to improve the quality of the waste, a combination of filtration and phytoremediation using the symbiosis of water hyacinth and calamus plants were applied. This study aimed to analyse the effectiveness of the filtration and phytoremediation processes using a combination of the two aquatic plants. The method used in this study was an experimental method with the treatment of a comparison of water hyacinth and calamus, namely 25%:75%, 50%:50%, and 75%:25%. The research stages are the acclimatization of the two aquatic plants for ten days, filtration with sand, gravel, and coconut fibers, and phytoremediation. The parameters tested in this study were BOD and COD. The results showed that the filtration and phytoremediation treatment with a combination of water hyacinth and jeringau could reduce the BOD and COD values on the 7th day with the highest level of effectiveness in reducing BOD obtained in treatment A2 with BOD levels of 15.21 mg/L or decreased by 80, 65% and the largest COD decrease was in the A3 treatment with a COD value of 797.5 mg/l or decreased by 14.99% from the initial COD value.